Proceedings of the Web Conference 2020 2020
DOI: 10.1145/3366423.3380206
|View full text |Cite
|
Sign up to set email alerts
|

Abstractive Snippet Generation

Abstract: An abstractive snippet is an originally created piece of text to summarize a web page on a search engine results page. Compared to the conventional extractive snippets, which are generated by extracting phrases and sentences verbatim from a web page, abstractive snippets circumvent copyright issues; even more interesting is the fact that they open the door for personalization. Abstractive snippets have been evaluated as equally powerful in terms of user acceptance and expressiveness-but the key question remain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…On the other hand, extractive explanations by LIME are likely to be relevant to the document, and do not require the same evaluations as abstractive explanations by GenEx. Note that abstractive generation of texts at the level of noun-phrase has a lower risk of topic drift compared to abstractive snippet generation which has been motivated recently [7], and is confirmed by the results of human evaluation on relevance to document content.…”
Section: Explanations Qualitysupporting
confidence: 63%
See 1 more Smart Citation
“…On the other hand, extractive explanations by LIME are likely to be relevant to the document, and do not require the same evaluations as abstractive explanations by GenEx. Note that abstractive generation of texts at the level of noun-phrase has a lower risk of topic drift compared to abstractive snippet generation which has been motivated recently [7], and is confirmed by the results of human evaluation on relevance to document content.…”
Section: Explanations Qualitysupporting
confidence: 63%
“…Bast and Celikik [5] proposed an efficient solution for extractive snippets by taking advantage of inverted index, a popular data structure used in most information retrieval systems. Recently, Chen et al [7] proposed abstractive snippet generation as a potential solution to circumvent copyright issues. The authors demonstrated that despite the popularity of extractive snippets in the current search engines, abstractive summarization is equally powerful in terms of user acceptance and expressiveness.…”
Section: Snippet Generationmentioning
confidence: 99%
“…Therefore, search snippet generation can be considered as one kind of Query-focused Summarization (QFS). Similar to generic document summarization, this body of work can also be divided into extractive approaches (Zhu et al, 2019;Feigenblat et al, 2017;Roitman et al, 2020) and abstractive approaches (Laskar et al, 2020a;Baumel et al, 2018;Chen et al, 2020a;Su et al, 2020;Laskar et al, 2020b). As some PTMs are proved to be effective in text generation, most existing work adopted PTMs to generate abstractive snippets.…”
Section: Snippet Generationmentioning
confidence: 99%
“…Suitable datasets include DUC 2004, DUC 2005, and DUC 2006, which contain query-based (multi-)document summaries (DUC). Webis-Snippet-20 consists of 10M web pages together with their query-based abstractive snippets (Chen et al, 2020). In these datasets, each document (or set of documents) has one or more summaries with respect to a single query.…”
Section: Related Workmentioning
confidence: 99%